New rice variety for swamps - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A new variety of rice that outyields all existing varieties and matures faster has been developed by the West African Rice Development Association. The new variety, ROHYB 1 5-WAR-3-3-B-2, has been developed by cross-breeding varieties from other...